An Innovation Study on Luggage Wheel Design for Seamless Travel - Kurudirek, Abdullah; Kurudirek, Melek Azra; Kurudirek, Kadriye Afra (Compiler, 2025)
In this paper, a new suitcase study that will enable people to travel comfortably in every aspect is emphasized, and prototype examples are handled. This study reveals the latest innovations in suitcase design aimed at improving travel efficiency and eliminating wheel malfunctions that may occur in the suitcases carried by passengers (especially breakages during loading and unloading in the cargo section). Considering current design trends and the smoothness of travel, as well as the joy of passengers being able to securely retrieve their suitcases from the conveyor belts at their destinations, this research identifies the key features that contribute to enhanced mobility and comfort. This study employs a mixed-methods approach combining both qualitative user feedback and quantitative data to evaluate performance. A total of 60 participants (30 male, 30 female) were included in real-world testing scenarios, while durability tests were conducted under controlled laboratory conditions. Both quantitative and qualitative results indicate that the newly developed suitcase design outperformed standard wheels, especially within the 20–32 kg weight range, in terms of comfort, usability, durability, and overall user satisfaction.. Previous research findings indicate that modern design features such as ergonomic handles and lightweight materials significantly enhance travel comfort and efficiency. In this research, the latest wheel designs are expected to contribute to these findings. Throughout this research, we will look at two separate prototype examples to illustrate these cutting-edge concepts simply and understandably. Therefore, this article provides insights for designers, manufacturers, and travellers interested in maintaining the robust functionality of suitcases.